The Effects of Repetitive Transcranial Magnetic Stimulation on Anxiety in Patients With Moderate to Severe Traumatic Brain Injury: A Post-hoc Analysis of a Randomized Clinical Trial - Rodrigues, Priscila Aparecida; Zaninotto, Ana Luiza; Ventresca, Hayden M.; Neville, Iuri Santana; Hayashi, Cintya Yukie; Brunoni, Andre R.; de Paula Guirado, Vinicius Monteiro; Teixeira, Manoel Jacobsen; Paiva, Wellingson Silva (Frontiers in Neurology, 2020)
Background: Traumatic brain injury (TBI) is one of the leading causes of neuropsychiatric disorders in young adults. Repetitive Transcranial Magnetic Stimulation (rTMS) has been shown to improve psychiatric symptoms in other neurologic disorders, such as focal epilepsy, Parkinson’s disease, and fibromyalgia. However, the efficacy of rTMS as a treatment for anxiety in persons with TBI has never been investigated. This exploratory post hoc analyzes the effects of rTMS on anxiety, depression and executive function in participants with moderate to severe chronic TBI. Methods: Thirty-six participants with moderate to severe TBI and anxiety symptoms were randomly assigned to an active or sham rTMS condition in a 1:1 ratio. A 10-session protocol was used with 10-Hz rTMS stimulation over the left dorsolateral prefrontal cortex (DLPFC) for 20 minutes each session, a total of 2000 pulses were applied at each daily session (40 stimuli/train, 50 trains). Anxiety symptoms; depression and executive function were analyzed at baseline, after the last rTMS session, and 90 days post intervention. Results: Twenty-seven participants completed the entire protocol and were included in the post hoc analysis. Statistical analysis showed no interaction of group and time (p>0.05) on anxiety scores. Both groups improved depressive and executive functions over time, without time and group interaction (ps<0.05). No adverse effects were reported in either intervention group. Conclusion: rTMS did not improve anxiety symptoms following high frequency rTMS in persons with moderate to severe TBI.